Pembuatan Tepung Telur Ayam (Gallus gallus. D) Asin Rebus - Andriyani, Yulita Andina; Tamrin, Tamrin; Kuncoro, Sapto; Warji, Warji (Jurnal Agricultural Biosystem Engineering, 2023)
Chicken eggs are a food that is very rich in nutrients, including protein (12.8%) and fat (11.8%). The high levels of water, fat and protein in eggs can make them a good medium for bacterial growth. Quality deterioration in eggs can be prevented by using egg preservation methods, namely drying eggs into egg powder or flour. Chicken eggs are still very limited and inefficient processing to be used as salted egg flour. Therefore, it is necessary to conduct research on the manufacture of boiled salted chicken egg flour (Gallus gallus. D). This research was conducted to study the making of boiled salted chicken egg flour and understand the characteristics by taking measurements on whole eggs, egg whites, and yolks using the proximate test method, measurement of fineness, and color test. This research was conducted using a non-factorial Completely Randomized Design (CRD) model consisting of 6 testing factors (T) and (A), namely: T1 whole unsalted chicken eggs, T2 white unsalted chicken eggs, T3 yellow unsalted chicken eggs, A1 whole salted chicken eggs, A2 white salted chicken eggs, and A3 yellow salted chicken eggs. The research results of salted chicken egg flour making is a process that involves drying salted eggs and grinding them into flour form. The preparation of salted egg flour showed that the difference between regular chicken eggs and salted chicken eggs, which resulted, affected the proximate properties and had a noticeable impact on the nutritional composition and physical properties of the egg flour produced, while the moisture content was not significantly different. Keywords: Chicken Egg Flour, Egg Preservation, Proximate Properties, Salted Eggs.